(untitled) - Clow, Archibald (London, 1952)
Contents: Minerals and Manufactures, The economy of common salt, The trade in ashes and kelp, The palaeotechnic transition, Soap,...
Keywords: Technological chemistry,Công nghệ hóa học; History,Lịch sử